A 3D joint interpretation of magnetotelluric and seismic tomographic models: The case of the volcanic island of Tenerife. (December 2017) - García-Yeguas, Araceli; Ledo, Juanjo; Piña-Varas, Perla; Prudencio, Janire; Queralt, Pilar; Marcuello, Alex; Ibañez, Jesús M.; Benjumea, Beatriz; Sánchez-Alzola, Alberto; Pérez, Nemesio
Abstract: In this work we have done a 3D joint interpretation of magnetotelluric and seismic tomography models. Previously we have described different techniques to infer the inner structure of the Earth. We have focused on volcanic regions, specifically on Tenerife Island volcano (Canary Islands, Spain). In this area, magnetotelluric and seismic tomography studies have been done separately. The novelty of the present work is the combination of both techniques in Tenerife Island. For this aim we have applied Fuzzy Clusters Method at different depths obtaining several clusters or classes. From the results, a geothermal system has been inferred below Teide volcano, in the center of Tenerife Island. An edifice hydrothermally altered and full of fluids is situated below Teide, ending at 600 m below sea level. From this depth the resistivity and VP values increase downwards. We also observe a clay cap structure, a typical feature in geothermal systems related with low resistivity and low VP values. Highlights: We perform a 3D joint interpretation of magnetotelluric and seismic tomography models. We apply Fuzzy Clusters Method at different depths obtaining several clusters or classes. We infer a geothermal system, including a clay clap structure, below Teide volcano.